السّلالم الحجاجية في التّفسير اللّغوي للقرآن الكريم -دراسة في كتاب الدّر المصون للسّمين الحلبي - عيادي, منى; حرزولي, العزوزي (جامعة الوادي - University of Eloued, 2023)
يسعى هذا المقال إلى إبراز الآليات الحجاجية التي يبنى عليها التفسير اللّغويّ, والتي من شأنها أن تسهّل من عملية التواصل, ويتضح أن اللّغة الواصفة للقرآن الكريم في تفسير الدّر المصون مبنية وفق نظام إقناعي تأثيري, ليحدث أثرا في نفوس المتلقين ويؤدي إلى الإقناع بدرجة التبكيت, بحيث أنّ السّمين الحلبي في درّه قد وظّف تقانات السلالم الحجاجية, ومما تتكون عليه من قوانين درجية تتوسطها مجموعة الرّوابط لتوضح الدّور الحجاجي في ما يكمنّ, والتيتسير وفق منحى تصاعدي بغية الوصول إلى نتائج محددة, ومن خلال دراستنا سنوضح السّلالم الحجاجية انطلاقا من كتاب الدّر المصون في علوم الكتاب المكنون للسّمين الحلبي Abstract; This paper aims at demonstrating the argumentative mechanisms that the linguistic interpretation is drawn upon. Which can facilitate communication. It is shown that the language used describing the Qur'an in the book Tafsir Addor Al Massoun is based on a persuasive and influential system, in order to make an impact in the audiences' souls and convince them to the extent of repentance. Al Samin Al Hallabi in his book Al Dor Al Massoun used the argumentative scales technics and their gradual rules which contain a group of ties to demonstrate where the argumentative role lies. It goes according to an ascending approach in order to reach specific conclusions, And through our study we will demonstrate the argumentative scales starting from the book Al Dor Al Massoun Fi Al kitab Al Maknoun which is written by Al Samin Al Hallabi
Pilgrims' Ladders In The Linguistic Interpretation Of The Holy Qur'an Study In The Book Al-durr Al-masoon By Samin Al-halabi
Article
Keywords: لحجاج ؛ السّلالم الحجاجية؛ التّفسير اللّغوي؛ السّمين الحلبي؛ الدّر المصونا; Argumentation; Orbital staircases ; Linguistic Interpretation; Al-Durr Al-massoon ; Al-Samin Al Halabi.